1995
DOI: 10.1620/tjem.176.69
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nitric Oxide Synthase Activities in the Cerebellum during Development and Aging of C57BL/6 Mice.

Abstract: Nitric oxide (NO) is one of the neurotransmitters in the cerebellum. Activities of NO synthase and densities of granule cells were determined in the cerebellum in an attempt to elucidate a mechanism of biochemical changes on the anatomical basis during aging. Activities of Cat+/calmoduline dependent NO synthase were measured in the cerebellum in male and female mice, from 18 gestation days to 28 months of age. There were significant differences in NO synthase activities among the groups of prenatal (18 gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Our own observation was that only striatum and olfactory cortex from aged rats showed a decrease in the activity and the expression of nNOS, but iNOS did not change in any of the considered areas [135]. Several other studies on aged animals have demonstrated regionally variable decrease of either catalytic activity or NOS expression/localization, with emerging discrepancies concerning the brain areas to which those alterations were located [234,[236][237][238][239]. Recently, it has been demonstrated that nNOS significantly decreases in the hippocampi from congnitively impaired aged rats only [240].…”
Section: Neuropathological Role Of Nitric Oxidementioning
confidence: 76%
“…Our own observation was that only striatum and olfactory cortex from aged rats showed a decrease in the activity and the expression of nNOS, but iNOS did not change in any of the considered areas [135]. Several other studies on aged animals have demonstrated regionally variable decrease of either catalytic activity or NOS expression/localization, with emerging discrepancies concerning the brain areas to which those alterations were located [234,[236][237][238][239]. Recently, it has been demonstrated that nNOS significantly decreases in the hippocampi from congnitively impaired aged rats only [240].…”
Section: Neuropathological Role Of Nitric Oxidementioning
confidence: 76%
“…There is a wealth of molecular and cellular phenomena, whose biological significance has been inferred experimentally, that could be incorporated into a realistic cerebellar model in order to investigate their implications for function. These include: the role of specific ionic channel properties in regulating neuronal excitation (amongst known examples see Jaeger et al, 1997 ; Bower and Beeman, 1998 ; Kubota and Bower, 2001 ; Ovsepian et al, 2013 ); the role of synaptic receptor properties in neuronal excitation and plasticity, like the voltage-dependence of NMDA receptor subtypes (Schwartz et al, 2012 ); the role of diffusible messengers like nitric oxide in coordinating long-term synaptic plasticity (Garthwaite, 2016 ); the role of intracellular biochemical cascades in the induction and expression of long-term synaptic plasticity (Tsukada et al, 1995 ; Schweighofer and Ferriol, 2000 ; Billings et al, 2014 ).…”
Section: Current Perspectives For Realistic Cerebellar Modelingmentioning
confidence: 99%
“…Our finding of 84% declines in a3-mRNA content per PC supports a considerable alteration of some kind in neuronal activity before cell dropout. The 43% decline in granular cell a1-mRNA may be pertinent to the observed reduction in nitric oxide synthase (NOS) expression in granular cells (Tsukada et al, 1995) and the possible reduction in parallel fibers in the ML (Rogers et al, 1984). The reduced level of a1-mRNA may reflect a reduced granular cell activity that is critical to the level of activity in the PCs.…”
Section: Possible Significance Of the Altered Expression Of A-isoformmentioning
confidence: 99%